Analysis of Calculation of Dimensions of Irrigation Channels in Bondoyudo Irrigation Areas - Otong Kuncoro; F.Rooslan Edy Santosa (Journal of World Conference (JWC), 2022)
The Bondoyudo Irrigation Area, which is located in Lumajang Regency and Jember Regency, is one of the irrigation systems that has great potential to be developed to improve the living standards of rural communities, especially those who use water for agriculture. And it is also e xpected to support government programs in the context of the continuity of the food security program in Indonesia. So it is necessary to analyze the dimensions of the irrigation canals of the Bondoyudo Irrigation Area, in order to determine the ideal irrigation channel design and in accordance with the planned discharge, so as to create an irrigation channel that can work optimally. Rainfall data in the form of daily rainfall data recorded at rain stations that are within the coverage of irrigation areas: Umbul Station, Sumber Pandan Station, Kedung Jajang Station, Mount Ringgit Station. Meanwhile, Climatological Data in the form of data on duration of sunlight, humidity, average air temperature, and wind speed were collected from the Agroclimatology Station of PG Semboro. From the calculation of effective rainfall for the largest rice plant, namely 1.99 mm/day while for secondary crops it is 1.42 mm/day, and several alternative results of irrigation water needs, there is the smallest maximum water requirement value of 2.16 lt/sec. /ha which occurred in November. Meanwhile, from the calculation of the dimensions of the Bondoyudo primary channel, the design discharge is 21.68 wet circumference 50 m, cross - sectional area 144 m2, hydraulic radius 2.88 m, flow velocity is 0.0288 and flow rate based on the Strickler formula is 3.121 m3/s with a trapezoidal cross-sectional shape. the water level from the bottom of the primary channel is 2 m, the width of the channel bottom is 15 m with a slope of 1:1 and a guard height of 0.40 m.